Avaliação do internato médico em uma unidade de pronto atendimento, sob a perspectiva dos alunos, para proposição de modelo curricular em urgências clínicas ao colegiado do curso de Medicina da Faculdade de Ciências Médicas e da Saúde de Sorocaba - PUCSP - Campos, Maria Celeste Gonçalves (2013)
The medical course at the Faculdade de Ciências Médicas e da Saúde of PUC-SP in Sorocaba (SP, Brazil) went through changes in its curricular model, which were motivated by various factors. Some of them can be traced back to the creation of the Unified Health System (SUS) and, afterwards, to the creation of the National Curricular Guidelines for the Medical Course. Therefore, as recommended by the Guidelines, there was, starting in 2006, an amplification of the practical scenarios, which resulted in the insertion of the student in the secondary level of attention to urgencies in a Unity of First Care (UPA). The UPA occupies an important role in the Urgency Service Network, which was established by the federal government in July 2011. The Network was created with the objective of qualifying the services for the Brazilian citizen in a situation of urgency in any of the gateways to the SUS, with emphasis in prevention, treatment and recover of the main causes of morbimortality in the Brazilian population: Trauma, Cerebral Vascular Accident and Acute Myocardial Infarction. This insertion of FCMS students in the UPA occurred in 2010, with fifth year interns of the pediatric internship. In 2011, the same interns, now in their sixth year, started to attend the clinical medicine internship in the same unit. Objectives: Evaluate the clinical medicine internship at the UPA in the eyes of the undergraduates and offer resources to the urgencies curriculum of the FCMS. Materials and Methods: The scenario was evaluated through the analysis of data pertaining to the services provided in the unit during the year of 2011 and the services conducted by students during May of 2012. The internship was evaluated using a semi-structured questionnaire applied to the interns of the year 2012. A study was also done to verify how urgency-related themes were presented to the students of the years one through four with basis on online material available on the Moodle platform of the FCMS in the year 2012. Results: The results showed that the students were pleased by many factors, like the practical learning and practical training; the large volume of patients, which allows contact with the most prevalent diseases of the community; and the constant presence of the teacher. The most attention-worthy occurrences were the large number of patients who requested a medical certificate to justify their absence from work, the cases of low back pain, the cases of thoracic pain of possible isquemic origin and the cases of respiratory diseases. Among the negative points cited were the duration of the internship, which was considered short; the demand for medical certificates; the distance between the unity and the school; and the small number of service rooms in some occasions. Their suggestions were an increased course load, more service rooms and more theoretical classes. The data of the dissertation, alongside the theoretical background research for its execution, allowed the elaboration of the Matrices of Competence to be developed throughout the internship. Conclusion: The internship was approved by this group of students. The scenario at the UPA can be an alternative for the teaching of urgencies. The elaboration of the matrices alongside the identification of learning opportunities throughout the course can propitiate a longitudinal approach to teaching